Obesity, Psychological Health and Eating Behaviour Patterns of Sultan Idris Education University Students in Malaysia - Khan, Abdul Mujeeb; Abdul Wahab Khan , Rahmatullah Khan; Shahadan, Azman (International Journal of Psychosocial Rehabilitation, 2020)
Obesity in Malaysia is increasing rapidly. World Health Organization survey-2010 ranked Malaysia as sixth in Asia with highest adult obesity rate. Obesity contributes in severe health problems, drastically reduces quality of life and causes psychosocial problems. College/university is a critical period regarding unhealthy changes in eating behaviours among students. This study investigated the association between eating behaviour and obesity. The study examined differences in the eating behaviour of normal, overweight and obese students and their Psychological health at University Pendidikan Sultan Idris-(UPSI). The purpose was to examine university student’s eating behaviour as a contributing factor to obesity. Methods: Cross-Sectional study was conducted among 100 respondents based on convenient sampling. Information on respondent’s demographic characteristics and Body Mass Index (weight & height) were obtained. General Health Questionnaire-28 was used to measure psychological aspects of eating behaviour with original English version. While Eating Inventory was used to measure three dimensions: disinhibition, hunger and cognitive restraint of eating behaviour among three groups obese, overweight and normal weight students. One-Way ANOVA was used to compare eating behaviour. Results: Data analysis showed that obese students and overweight students had different eating behaviour, F(97,2)=2.87, p≤05. Overweight students had better control on eating behaviour as compared to obese students. There is tendency of significant difference between Obese students (MDis+Hung =11.71, S.D.=4.74) and overweight (MDis+Hung=8.68, S.D.=4.64) group for subscale Disinhibition+Hunger, F(2,97)=2.89, p=0.06. Conclusion: Obese students have no insight on eating-preferences (E.g. less calories, low fat food consumption) and less control on eating behaviour. They face more psychological issues compared to non-obese students.Keywords: Eating Behaviour, Obesity, Comparative Study, University Students.